Policy networks and policy change putting policy network theory to the test - Compston, Hugh 1955- (Hampshire, England Palgrave Macmillan, 2009)
"This study applies policy network theory to major technological, economic, environmental and social trends to generate propositions about the future of public policy. Among the findings are that we should expect more business-friendly policies, more intrusive law enforcement, more women-friendly policies, and stronger climate policies"--Provided by publisher
Machine generated contents note: Introduction * Policy Networks and Resource Dependency * Actors and Resources * Policy Network Theory as a Theory of Policy Change * Policy Network Theory and the Future of Public Policy * Testing Policy Network Theory * Policy Implications of Technological Trends * Growing Affluence, the Shift to Services, and the Growth of Womens Employment * Energy Use,Mobility and Climate Change * Trade Expansion and the Internationalization of Production and Finance * Sex and Secularization * Population Ageing and the Expansion of Education * The Future of Public Policy Introduction * Policy Networks and Resource Dependency * Actors and Resources * Policy Network Theory as a Theory of Policy Change * Policy Network Theory and the Future of Public Policy * Testing Policy Network Theory * Policy Implications of Technological Trends * Growing Affluence, the Shift to Services, and the Growth of Womens Employment* Energy Use, Mobility and Climate Change * Trade Expansion and the Internationalization of Production and Finance * Sex and Secularization * Population Ageing and the Expansion of Education * The Future of Public Policy
Includes bibliographical references (p. 237-257) and index.
Keywords: Policy networks; Policy sciences; Social history